A4 6 Freddy Fazbear’s Power Plant - Savic, Natasha; Birch, Hannah; Tzabach, Lee (Physics Special Topics, 2023)
In this paper, we investigate how much energy is required to keep the animatronics at Freddy Fazbear’s Pizzeria constantly running since the closure of the restaurant. To do this, we calculate the average energy used by an industrial robot working constantly for roughly 7 years. We find that, to keep the animatronics constantly running for this amount of time, a total of 6.6 × 10^11 J are required for each of them, or 6.1 × 10^7 AA batteries.